Effects of increasing added choice white grease in corn and sorghum-based diets on growth performance and fat quality characteristics of finishing pigs - J M Benz; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
One hundred twenty crossbred barrows and gilts (TR4 × 1050) with an initial weight of 119.9 lb were used in an 83-d experiment to evaluate the effects of increasing added fat to corn or sorghum-based diets on growth performance and fat quality characteristics of finishing pigs. Treatments were arranged in a 2 × 2 × 3 factorial based on grain source (corn or sorghum), gender, and added fat (0, 2.5, or 5% choice white grease, CWG). At the end of the trial, jowl fat and backfat samples were collected. Pigs fed sorghum-based diets had increased (P<0.01) ADG compared with pigs fed corn-based diets. Pigs fed increasing CWG had increased (P<0.01) ADG. Pigs fed corn-based diets tended to have improved (P<0.06) dressing percentage, 10th rib BF, and percentage lean when compared with pigs fed sorghum-based diets. Barrows tended to have greater (P<0.06) dressing percentage and decreased (P<0.07) percentage lean when compared to gilts. Pigs fed increasing CWG had increased (P<0.02) 10th rib backfat, tended to have increased (P<0.08) hot carcass weight, and tended to have decreased (P<0.07) percentage lean. There was a fat level by grain source interaction (P<0.03) for percent C 18:2 fatty acids and iodine value in jowl fat. The interaction was due to the greatest increase in IV and percentage C 18:2 fatty acids occurring when CWG was increased from 2.5 to 5% for corn-based diets, while the greatest increase was from 0 to 2.5% CWG for sorghum-based diets. Despite this interaction, adding CWG increased (linear, P<0.02) percentage C 18:2 fatty acids and iodine value in jowl fat. Pigs fed corn-based diets had increased (P<0.01) iodine values and percentage C 18:2 fatty acids in jowl fat and backfat compared with pigs fed sorghum-based diets. Increasing dietary CWG increased (P<0.01) iodine value in jowl fat and backfat, increased (P<0.01) percentage C 18:2 fatty acids in backfat, tended to increase (P<0.06) percentage 18:2 fatty acids in jowl fat, and decreased (P<0.01) percentage saturated fatty acids in jowl fat and backfat. In summary, substituting sorghum for corn in diets for finishing pigs can be an effective way to reduce iodine value without affecting growth.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; Corn; Fat; Feed ingredients; Pork quality; Sorghum